2020
DOI: 10.1007/s13178-020-00433-1
|View full text |Cite
|
Sign up to set email alerts
|

On the Outskirts of the Charmed Circle—Challenges and Limitations of Sexual Health Promotion to Young People in Secure State Care

Abstract: Objectives Young people on the verge of, or in, secure state care or incarceration have reduced general and sexual health. The promoting of sexual health among young people in secure state care is therefore a responsibility for both the state-run agency responsible for this care and for the professionals who work there. Methods This position paper discusses sexual and reproductive health and rights (SRHR) for young people in secure state care in Sweden. Four previous studies on sexual health of young people in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Last, but not least, the social workers suggest ways forward, thereby showing they are creating a trustful alliance. Overall, our findings are consistent with previous research that indicates that social care systems face difficulties meeting the needs of transgender and nonbinary youth (Erney & Weber, 2018;Gerassi & Pederson, 2022;Greeno et al, 2022;Kaasbøll et al, 2022;Lindroth, 2021;Mallon, 2019;Mountz et al, 2018;Schaub et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Last, but not least, the social workers suggest ways forward, thereby showing they are creating a trustful alliance. Overall, our findings are consistent with previous research that indicates that social care systems face difficulties meeting the needs of transgender and nonbinary youth (Erney & Weber, 2018;Gerassi & Pederson, 2022;Greeno et al, 2022;Kaasbøll et al, 2022;Lindroth, 2021;Mallon, 2019;Mountz et al, 2018;Schaub et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Substance use is one of the reasons why they are placed in these institutions. However, the findings underscore the need to include support on matters of sexuality in social work when individuals are exiting substance use (Lindroth, 2020;Skårner et al, 2016;Svensson & Skårner, 2014;Wikström et al, 2018). Regarding their most recent sexual experience, young women in secure state care appear to have experienced less power and stated that they were more unsafe compared to the other three groups.…”
Section: Social Work Implications In Relation To Sexual Attitudes and Experiencesmentioning
confidence: 81%
“…Similarly, young people subjected to secure state care in Sweden who display non-normative or unconventional sexual behaviours or experiences risk being met with unprofessionalism. It is suggested that young people therefore filter what experiences are societally acceptable to share with professionals, who in turn are not educationally equipped to work with sexual health promotion (Lindroth, 2020).…”
Section: Srhr-affirmative Social Work With Young Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…Yes, self-testing has been positively adopted by gbMSM and has led to an increase in HIV testing overall; however, as we have stated, this is potentially due in large part to the real and perceived shortcomings within the traditional HIV prevention armamentarium. For gbMSM, who exist on the outskirts of Rubin’s charmed circle of sexuality, their ability to interface with the traditional healthcare system is dramatically reduced and they are frequently put into positions where they must find ways to help themselves or risk receiving no help at all ( Kinsler et al, 2007 ; Rubin, 2007 ; Lindroth, 2021 ; Kipke et al, 2007 ). Considering this, the uptake of self-testing can be read as a symptom of a persistent limitation of the current healthcare system, specifically its inability to take into account the sociocultural context of gbMSM who are younger and/or identify as BIPOC.…”
Section: Discussionmentioning
confidence: 99%